Heat dermabrasion as an effective innovative technique for treatment of different types of scars - Jabbar, Raed; Sharquie, Khalifa (Journal of Pakistan Association of Dermatologists, 2022)
Background There are different morphological types of scars like linear, rounded with regular linear or irregular surface according to the cause could be induced by trauma or skin disorders like cutaneous leishmaniasis. Objective To modify scars by heat dermabrasion, to have a better appearance with good cosmetic look. Methods This is a prospective study where 74 patients included, 39(52.7%) females and 35(47.29%) males, their ages ranged from 5-40 years with a median age of 25 years. According to the shape, nature and color, there were linear, rounded, pigmented, atrophic or non-atrophic scars, with irregular or smooth surface. The scoring system was adjusted according to the type of scar including a reduction in surface area, normalize the texture, suture lines, atrophy and pigmentation. So the estimation of the reduction rates in all these points was as follow: mild reduction: 1-25%, moderate reduction: >25-50%, marked reduction: >50-75%, and excellent reduction: >75-100%. Diathermy was applied directly to scar to induce destruction of old scar. Results The cause of the scar was traumatic in 60(81%) patients while by disease process commonly leishmaniasis in 14(18.9%) cases. There was gradual healing, remodelly and improvement of all types of scar during six months follow up. The scoring reduction rate showed moderate in 30(40.54%) patients while marked in 35(47.2%) cases and 9(12.16%) cases had excellent improvement. Conclusion Heat dermabrasion is an innovative good cosmetic cost effective therapy for different types of scars without need for surgical excision and suturing.